2015
DOI: 10.1038/leu.2015.240
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: SAR650984 directly induces multiple myeloma cell death via lysosomal-associated and apoptotic pathways, which is further enhanced by pomalidomide

Abstract: The anti-CD38 monoclonal antibody SAR650984 (SAR) is showing promising clinical activity in treatment of relapsed and refractory multiple myeloma (MM). Besides effector-mediated antibody-dependent cellular cytotoxicity and complement-mediated cytotoxicity, we here define molecular mechanisms of SAR-directed MM cell death and enhanced anti-MM activity triggered by SAR with Pomalidomide (Pom). Without Fc-cross-linking agents or effector cells, SAR specifically induces homotypic aggregation (HA)-associated cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
207
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(215 citation statements)
references
References 43 publications
2
207
1
5
Order By: Relevance
“…However, on the Burkitt's lymphoma cell line Ramos we did show caspase-3 activation upon cross-linking of DARA with secondary Ab (8). The homotypic aggregation-related caspase-independent and -dependent PCD was also shown for SAR650984, a chimeric CD38 Ab (40,41), in the absence of secondary cross-linking. Nonetheless, we have previously shown that the direct effect of SAR650984 to induce PCD is comparable to DARA-induced PCD in the presence of a secondary Ab (8).…”
Section: Discussionmentioning
confidence: 97%
“…However, on the Burkitt's lymphoma cell line Ramos we did show caspase-3 activation upon cross-linking of DARA with secondary Ab (8). The homotypic aggregation-related caspase-independent and -dependent PCD was also shown for SAR650984, a chimeric CD38 Ab (40,41), in the absence of secondary cross-linking. Nonetheless, we have previously shown that the direct effect of SAR650984 to induce PCD is comparable to DARA-induced PCD in the presence of a secondary Ab (8).…”
Section: Discussionmentioning
confidence: 97%
“…CD38, which is frequently expressed in MM cells, is also induced during OC formation, as analyzed by immunoblotting ( Figure 1C and 6A) and flow cytometry ( Figure 6B). Because anti-CD38 mAbs recently showed a clinical benefit in relapsed and refractory MM patients, 29,30 we further addressed whether an anti-CD38 mAb SAR650984 (SAR) 31 has any impact on OCs. We cultured CD14…”
Section: Cd38 Is Induced During Oc Formationmentioning
confidence: 99%
“…Isa, like dara, induces MM cell lysis via multiple effector cell-dependent mechanisms including antibody-dependent cellular cytotoxicity (ADCC), complement dependent cytotoxicity (CDC), and antibody-dependent phagocytosis (ADCP). In contrast to dara, isa directly kills MM cells via lysosomemediated cell death and apoptosis in the absence of Fc cross-linking agents or effector cells [3]. Furthermore, this direct toxicity is preferentially seen in myeloma cells expressing elevated levels of CD38 regardless of p53 mutations, which are common in the setting of RRMM.…”
Section: Yu-tzu Tai and Kenneth C Andersonmentioning
confidence: 99%